Possible signals of two QCD phase transitions at NICA-FAIR energies - Bugaev K. A.; Ivanytskyi A. I.; Sagun V. V.; Grinyuk B. E.; Savchenko D. O.; Zinovjev G. M.; Nikonov E. G.; Bravina L. V.; Zabrodin E. E.; Blaschke D. B.; Kabana S.; Taranenko A. V. (EPJ Web of Conferences, 2019)
The chemical freeze-out irregularities found with the most advanced hadron resonance gas model and possible signals of two QCD phase transitions are discussed. We have found that the center-of-mass collision energy range of tricritical endpoint of QCD phase diagram is [9; 9.2] GeV which is consistent both with the QCD inspired exactly solvable model and experimental findings.